2002
DOI: 10.4049/jimmunol.169.6.3301
|View full text |Cite
|
Sign up to set email alerts
|

Opsonization of HIV-1 by Semen Complement Enhances Infection of Human Epithelial Cells

Abstract: In the present study we demonstrate that both X4- and R5-tropic HIV-1 strains are able to infect the human epithelial cell line HT-29. Infection was enhanced 2-fold when HIV was added to semen before contact with the cell cultures. The enhancing effect of semen was complement dependent, as evidenced by blockage of generation of C3a/C3adesArg in semen by heat or EDTA treatment of semen and suppression of semen-dependent enhancement with mAbs directed to complement receptor type 3 (CD11b/CD18) and soluble CD16. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
80
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 39 publications
7
80
0
1
Order By: Relevance
“…In addition, proviral HIV-1 DNA was detected in iDC within 6 h of incubation with complement-opsonized HIV-1, the amounts of HIV-1 pol DNA measured by semiquantitative nested PCR being significantly higher in cells infected with opsonized HIV, as compared with cells infected with virus that had been preincubated with culture medium. These data extend previous observations on the enhancing effect of complement on infection of monocytes/macrophages (8, 9) and more recently of CD4-negative, complement receptor-positive epithelial cells (10). The role of complement receptor (CR3) was shown by the blocking effect of anti-CR3 mAbs on infection of iDC with opsonized HIV-1 BaL and HIV-1 NDK .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, proviral HIV-1 DNA was detected in iDC within 6 h of incubation with complement-opsonized HIV-1, the amounts of HIV-1 pol DNA measured by semiquantitative nested PCR being significantly higher in cells infected with opsonized HIV, as compared with cells infected with virus that had been preincubated with culture medium. These data extend previous observations on the enhancing effect of complement on infection of monocytes/macrophages (8, 9) and more recently of CD4-negative, complement receptor-positive epithelial cells (10). The role of complement receptor (CR3) was shown by the blocking effect of anti-CR3 mAbs on infection of iDC with opsonized HIV-1 BaL and HIV-1 NDK .…”
Section: Discussionsupporting
confidence: 77%
“…Opsonization of HIV-1 with complement results in enhancement of viral infection of T and B cell lines (6,7), primary PBMC (8), and primary monocytes/ macrophages (9). We have demonstrated that HIV particles activate complement in semen resulting in an ability to infect human CD4-negative epithelial cells in a complement-dependent fashion via CD11b/CD18 (CR3) (10). Recently, others have reported a crucial role of CR3 in the productive infection of dendritic cells (DC) 3 by C3-opsonized HIV (11).…”
mentioning
confidence: 99%
“…An aliquot of semen was heat-inactivated (HI) for 30 min at 56 uC. Virus, either HIV-1 BaL or HIV-1 RF was then incubated with fresh semen, used at a concentration of 25 %, HI semen or media for 1 h at 37 uC as previously described (Bouhlal et al, 2002). TZM-bl were seeded as described above and exposed to various concentrations of CV-N for 1 h prior to infection.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition of HIV-1 BaL and HIV-1 RF by CV-N was tested using TZM-bl cells, in the presence or absence of whole semen [used at final concentration of 12.5 % (v/v)]. HI of semen was performed in order to assess if any of the complement components had an effect on CV-N efficacy, since it is known that virus opsonization can enhance virus infectivity (Bouhlal et al, 2002).…”
Section: Cv-n Activity In the Presence Of Semenmentioning
confidence: 99%
“…Less is known about the ability of C3-opsonized pathogens to interact with receptors on epithelial cells, and the functional consequence of such C3-receptor-ligand interaction. Colonic and cervical epithelial cells can internalize opsonized HIV (20) and Neisseria gonorrhoea (21), respectively. This occurs through binding to CR3.…”
mentioning
confidence: 99%